Knowledge, Attitudes, and Practices of Exclusive Breastfeeding as a Family Planning Method among Nursing Mothers in Aiyekire Local Government Area, Ekiti State - Janet, Adetoro Oluwatomisin; Okoroafor, Obeka, Maxwell; OKIJIOLA, Adeola H.; Oluwaseyi, Aibinuomo Ayomide; Tolulope, Akande Deborah; Olatunji, Muideen Babatunde (Journal of Science in Medicine and Life, 2024)
Background: Exclusive breastfeeding (EBF) is recognized as a natural method of contraception through the Lactational Amenorrhea Method (LAM), particularly during the first six months postpartum. However, its effectiveness and adoption depend on awareness, perception, and practice among nursing mothers. This study investigates the perception and utilization of EBF as a contraceptive method among postpartum women. Methods: A cross-sectional study was conducted among 150 postpartum women using a structured questionnaire to collect data on their awareness, perception, and practice of EBF as a contraceptive. Descriptive statistics, including frequencies and percentages, were used to analyze the data. Results: Among respondents, 87.1% reported practicing EBF as a contraceptive, with 59.3% describing the experience as successful. While 96.4% indicated willingness to use EBF again, 27.9% had used additional contraceptive methods during the first six months postpartum. Regarding perception, 62.7% disagreed that EBF is unreliable, and 86.0% strongly agreed that EBF benefits both mother and child when properly practiced. However, 71.3% believed EBF should not be relied upon after menstruation resumes. Misconceptions about EBF’s suitability for women with health challenges were noted among 21.7% of respondents. Conclusion: The study reveals high levels of EBF awareness and practice but highlights gaps in knowledge about its limitations and concurrent contraceptive use. Comprehensive health education addressing these gaps is essential to maximize the benefits of EBF as a contraceptive method. Policymakers and healthcare providers must integrate family planning education into maternal and child health programs to enhance maternal and child health outcomes.